Coaching winning sales teams : insights from the world of sport and business - Chapman, Tim; Smith, Tony; Pickford, Lynn (Emerald Publishing, Ltd., 2020)
Great sales coaching positively impacts individual, team and organisational sales performance. However, in today's results-driven and time-poor business world, the embedding of sales coaching into everyday practice is often overlooked. This guide utilises the authors' own experiences of helping companies and individuals turn average, static and infrequent sales coaching regimes into successful business strategies for winning sales teams. Looking at the reality of sales coaching today, the book explores the how, what and why of sales coaching. Through extensive research into elite coaches in the world of business and sports the authors explore the mindset, skills and behaviours required to be a top sales coach. They also consider how to be coached. How the sales person can overcome any natural shyness, fear of performance critique and seek out specific, timely and actionable coaching feedback. Using the latest thinking in neuroleadership and psychology, the book outlines the nine key behaviours of a great coach and provides a range of practical sales coaching models, tools and techniques which can be easily integrated into a sales leaders every-day pressurised role. Coaching Winning Sales Teams is an essential read for sales leaders and professionals, alongside researchers and practitioners working in HR, Learning and Development and Sales Effectiveness.